Potensi penggunaan β-tricalcium phosphate sebagai bahan substiusi tulang - Eddy Eddy; Hillary v Aurenne Santoso (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Calcium phosphate has been widely used in bone regeneration applications. Originalkalsium fosfat merupakan biomaterial yang sering diaplikasikan ke dalam defek tulang dengan tidak memberikan efek toksik pada jaringan sehat.The most commonly used calcium phosphate are hydroxyapatite and β-tricalcium phosphate (β-TCP). β-TCP is one of the bioceramic materials that has chemical structure of β-Ca3(PO4)2. The use of β-TCP is widely used in medicine and dentistry as bone graft due to bone loss. β-TCP is used to fill and repair bone deficiencies to regenerative new bone formation. In dentistry, β-TCP can be used for periodontal disease therapy, pre-implant surgery to fill a post-extraction socket before implant application, post-surgical removal of benign tumors, post-endodontic bone healing such as apicoectomy and drug delivery. Various studies have shown β-TCP has better osteoconductive, biocompatible, biodegradable and bonding strength to bone tissue properties than hydroxyapatite. This article reviews the use of β-TCP as a substitute for hydroxyapatite in medicine and dentistry for bone substitution materials.